High physical activity vs. quality of the trunk position and the efficiency of core muscles among young males - Dominik Łakoma; Agnieszka Jankowicz-Szymańska (University of Applied Sciences in Tarnow, Poland, 2020)
Introduction: Physical activity is considered to be one of the keystones of a healthy lifestyle and an indispensable condition for correct body posture. The purpose of the study was to check the body posture of young males with above-average physical activity and how the position of the trunk changes after extending the arms forward. The frequency and intensity of back pain among males in the study were also analyzed. Material and methods: The study involved 50 young, healthy males, whose high daily physical activity was confirmed by the IPAQ questionnaire. Body height and weight were checked, and BMI was calculated. The position of the trunk in three planes was examined using the ultrasonic Zebris Pointer system. The examination was performed twice: in the habitual standing position and in the position taken from the Matthiass test: standing position with the arms in front of the trunk (90o). The data was prepared in the Statistica v13 program. Results: The male participants were characterized by an incorrect depth of physiological curvatures of the spine and asymmetry of  the position of the shoulder and pelvic girdles in the frontal plane. Extending the arms forward in a standing position resulted in flatter thoracic kyphosis, rounder lumbar lordosis and tilting the trunk backwards. Periodic pain sensation in the lumbar spine was reported by approximately 60% of participants. It was a mild pain that did not require painkillers. There were no significant relationships between the quality of the trunk position and pains in the lumbar region. Conclusions: High physical activity turned out to be insufficient to ensure correct body posture and efficiency of core muscles. Postural education should be a permanent element of health promotion programs aimed at increasing the quality of life.